Contribuição do sistema de gestão empresarial (SGE) à efetivação da estratégia de produção - Gonzalez, Cleber Camacho (Universidade Federal de São Carlos, 2008)
This work assumes that the success of an enterprise can be reached out more easily if the strategic hierarchies are respected. Thus, the decisions referring to the operational area ought to follow the paths proposed by the operation strategy, which should be subordinated to and coherent with the corporative strategy. Having this as a main basis, this study focuses on the strategic objectives of operations and, by means of case studies, it aims at verifying the contribution of enterprise management system (EMS) to its elaboration. The cases were studied aiming at knowing the performance objectives most valued by the company administration and the production function too. Next, this work studies in the operational area which traits of a EMS can mostly contribute in the effectiveness of these strategic objectives. Finally, an inventory about the utilization of the EMS is elaborated and a comparative analysis is carried out so that it is possible to identify the adequacy level existent. In order to get the reader acquainted to the themes discussed a bibliographical review was made and it covers Operation Strategy, Enterprise Management System and the Strategic Alignment between them. By the end of this study, it was possible to observe that the enterprise strategy has been communicating efficiently with the operational area and that the utilization of EMS contributes to the strategic effectiveness of operation. Nevertheless, it can be realized that this contribution could be more relevant in case the alignment between Operational areas and IT were worked out more elaboratedly. In relation to the alignment level, analyses did not show significant differences neither among the companies researched in spite of the fact they belong to different action areas, nor among different EMS or their versions.
Keywords: Estratégia de produção; Sistemas de informação gerencial; Alinhamento da estratégia; Operation Strategy; Enterprise Management System; Strategic Alignment; ENGENHARIAS::ENGENHARIA DE PRODUCAO